Elementary statistics a step by step approach (Boston McGraw-Hill, 2004)
Elementary Statistics: a step by step approach is for general beginning statistics courses with a basic algebra prerequisite. The book is non-theoretical, explaining concepts intuitively and teaching problem solving through worked examples and step-by -step instructions. This edition features increased emphasis on Excel, MINITAB, and the TI-83 Plus graphing calculator, computing technologies commonly used in such coureses. ... Publisher description.
Preface -- Ch. 1 The Nature of Probability and Statistics -- Ch. 2 Frequency Distributions and Graphs -- Ch. 3 Data Description -- Ch. 4 Probability and Counting Rules -- Ch. 5 Discrete Probability Distributions -- Ch. 6 The Normal Distribution -- Ch. 7 Confidence Intervals and Sample Size -- Ch. 8 Hypothesis Testing -- Ch. 9 Testing the Difference Between Two Means, Two Variances, and Two Proportions -- Ch. 10 Correlation and Regression -- Ch. 11 Other Chi-Square Tests -- Ch. 12 Analysis of Variance -- Ch. 13 Nonparametric Statistics -- Ch. 14 Sampling and Simulation -- Appendix A: Algebra Review -- Appendix B-1: Writing the Research Report -- Appendix B-2: Bayes's Theorem -- Appendix B-3: Alternate Method for the Standard Normal Distribution -- Appendix C: Tables -- Appendix D: Data Bank -- Appendix E: Glossary -- Appendix F: Bibliography -- Appendix G: Photo Credits -- Appendix H: Selected Answers -- Index -- Glossary of symbols (back endpapers).
Includes bibliographical references (p. 761-762) and index.
Table of contents also available on the World Wide Web.
System reqiurements for accompanying CD-ROM: Macintosh OS 8.x, 9.x, X; Windows 95, 98, 2000, XP; Netscape 4.x, 5.x, 6.x; Explorer 5.x, 6.x; Minimum 256 color display; 640 x 480 screen resolution; Internet access (preferred); 16bit sound capable; 16MB minimum recommended RAM; 40MB minimum virtual memory.
Keywords: Statistics; Estadâistica.; Statistik